2019
DOI: 10.1002/jcp.28188
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA FEZF1‐AS1 predicts poor prognosis and modulates pancreatic cancer cell proliferation and invasion through miR‐142/HIF‐1α and miR‐133a/EGFR upon hypoxia/normoxia

Abstract: Nowadays, pancreatic cancer (PC) remains the most lethal tumor, partially due to the invasive and treatment‐resistant phenotype induced by the extent of hypoxic stress within the tumor tissue. According to previous studies, miR‐142/HIF‐1α and miR‐133a/EGFR could modulate PC cell proliferation under hypoxic and normoxic conditions, respectively. In the present study, FEZF1‐AS1, a recently described oncogenic long noncoding RNA, was predicted to target both miR‐142 and miR‐133a; thus, we hypothesized that FEZF1‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…lncRNA FEZF1 antisense RNA 1 (FEZF1-AS1) is localized at the human chromosome 7q31.32, and is transcribed in the opposite direction of FEZF1 gene. FEZF1-AS1 has been shown to be up-regulated in tumor tissues and cells, and exert oncogenic effects on lung cancer [18–21], breast cancer [22], liver cancer [23,24], gastric cancer [25–27], colorectal cancer [28,29], pancreatic cancer [30,31], ovarian cancer [32], cervical cancer [33], osteosarcoma [34], nasopharyngeal carcinoma [35] and multiple myeloma [36]. However, the expression and function of FEZF1-AS1 was still fully unclear in retinoblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…lncRNA FEZF1 antisense RNA 1 (FEZF1-AS1) is localized at the human chromosome 7q31.32, and is transcribed in the opposite direction of FEZF1 gene. FEZF1-AS1 has been shown to be up-regulated in tumor tissues and cells, and exert oncogenic effects on lung cancer [18–21], breast cancer [22], liver cancer [23,24], gastric cancer [25–27], colorectal cancer [28,29], pancreatic cancer [30,31], ovarian cancer [32], cervical cancer [33], osteosarcoma [34], nasopharyngeal carcinoma [35] and multiple myeloma [36]. However, the expression and function of FEZF1-AS1 was still fully unclear in retinoblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence documented that dysregulation of lncRNAFEZF1-AS1 associated with many processes in tumor progression, including OS. For instance, previous studies indicated that FEZF1-AS1 was notably upregulated, and FEZF1-AS1 knockdown inhibited proliferation, invasion, epithelial-mesenchymal transition (EMT), and induced apoptosis in multiple cancers, such as colorectal cancer, 19 ovarian cancer, 16 pancreatic cancer, 17 gastric cancer, 32 and hepatocellular carcinoma. 33 Also, lncRNA FEZF1-AS1 has been found to be associated with Warburg effect in many cancers including colorectal cancer, 19 pancreatic ductal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, previous studies indicated that lncRNA MALAT1, 13 SNHG1, 14 and HOST2 15 were significantly up-regulated in OS tissues and cells. Notably, lncRNA FEZF1-AS1 was also reported to regulate tumor progression in various cancers, such as ovarian cancer, 16 pancreatic cancer, 17 and OS. 18 In addition, lncRNA FEZF1-AS1 was documented to participate in Warburg effect in colorectal cancer 19 and pancreatic ductal adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from PVT1 [42,43], various other lncRNAs exert their regulatory function on HIF-1α by acting as ceRNAs [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90]. See Table 2 for an overview of ceRNAs and their associated pathways in HIF regulation.…”
Section: Pvt1mentioning
confidence: 99%